Selenium compound protects corneal epithelium against oxidative stress. - Akihiro Higuchi; Hiroyoshi Inoue; Tetsuya Kawakita; Tadashi Ogishima; Kazuo Tsubota (PLoS ONE, 2012)
The ocular surface is strongly affected by oxidative stress, and anti-oxidative systems are maintained in corneal epithelial cells and tear fluid. Dry eye is recognized as an oxidative stress-induced disease. Selenium compound eye drops are expected to be a candidate for the treatment of dry eye. We estimated the efficacy of several selenium compounds in the treatment of dry eye using a dry eye rat model. All of the studied selenium compounds were uptaken into corneal epithelial cells in vitro. However, when the selenium compounds were administered as eye drops in the dry eye rat model, most of the selenium compounds did not show effectiveness except for Se-lactoferrin. Se-lactoferrin is a lactoferrin that we prepared that binds selenium instead of iron. Se-lactoferrin eye drops suppressed the up-regulated expression of heme oxygenase-1, cyclooxygenase-2, matrix metallopeptidase-9, and interleukin-6 and also suppressed 8-OHdG production in the cornea induced by surgical removal of the lacrimal glands. Compared with Se-lactoferrin, apolactoferrin eye drops weakly improved dry eye in high dose. The effect of Se-lactoferrin eye drops on dry eye is possibly due to the effect of selenium and also the effect of apolactoferrin. Se-lactoferrin is a candidate for the treatment of dry eye via regulation of oxidative stress in the corneal epithelium.